Unexpected words that become your best memories: How sentential constraint and word expectedness affect memory retrieval - Höltje, Gerrit; Bader, Regine; Meßmer, Julia A.; Zogaj, Doruntinë; Mecklinger, Axel (Frontiers in Human Neuroscience, 2025)
Much is known about how the strength of contextual support from strongly constraining (SC) and weakly constraining (WC) sentences influences the online processing of expected (EXP) and unexpected (UNEXP) sentence-ending words. In the present study, we investigated the long-term mnemonic consequences associated with the processing of contextually constraint words and used event-related potentials (ERPs) to explore the memory retrieval mechanisms at work. Furthermore, we investigated false memories for expected but unpresented words. If these unpresented words remained highly accessible in memory, their false recognition as familiar would manifest in a larger early frontal old/new effect, the putative ERP correlate of episodic familiarity. Behavioral results indicated that strongly expected and highly unexpected words were more likely to be recognized, whereas memory for moderately expected words was attenuated. However, the anticipated early frontal old/new effects in these conditions did not materialize. Instead, the retrieval of highly unexpected (SC-UNEXP) words was characterized by a late parietal old/new effect, reflecting a reliance on recollection-based processes. Unexpectedly, during retrieval SC-UNEXP words also evoked a late frontal positivity, a pattern usually associated with the inhibition of unpresented expected words during encoding. This suggests that the retrieval of these words reactivated inhibitory mechanisms akin to those activated during encoding. Additionally, expected lures that were correctly identified as new elicited a broadly distributed positive slow wave, indicative of recollective processing in support of a recall-to-reject strategy. This latter effect was observed irrespective of the predictive strength of the contextual support.